SINERJITAS KONSEP PENDIDIKAN ADAT BATAK DAN ISLAM DALAM MEMBANGUN KARAKTER BANGSA - Nurfin Sihotang (IAIN Padangsidimpuan, 2018)
Indonesia is famous for religious nation, because the population adheres to a religion that believes and civilized nation because every tribes have traditions, customs and culture of the proud, religion in this case Islam, and especially customs in this traditional Batak have the same universal values, Islam with dimensions of it’s samaiwi and traditional Batak with dimensions of it’s ardhi World are faced with the globalization era with advancements in information technology and science lead to positive and negative impacts while competing or interplay with each other that can fade the character of a nation to oversees and to the strengthening national character and show to the outside into the world that this nation is a religious nation and culture as well as good character, Islamic values and culture of indigenous education in this regard should be sincronized by vagabond and Islam.